Empathy to action: Child and adolescent out‐group attitudes and prosocial behaviors in a setting of intergroup conflict. Issue 2 (6th November 2019) - Taylor, Laura K.; O'Driscoll, Dean; Dautel, Jocelyn B.; McKeown, Shelley
Abstract: The paper explored how to promote constructive intergroup relations among children and young people in a context of protracted conflict. Across two studies, the Empathy–Attitudes–Action model was examined in middle childhood and adolescence. More specifically, we tested the relations among dispositional empathy, out‐group attitudes, and prosocial behaviors for youth born after the peace agreement in Northern Ireland. In one correlational (Study 1: N = 132; 6–11 years old: M = 8.42 years, SD = 1.23) and one longitudinal design (Study 2: N = 466; 14–15 years old), bootstrapped mediation analyses revealed that empathy was associated with more positive attitudes toward the conflict‐related out‐group, which in turn, was related to higher out‐group prosocial behaviors, both self‐report and concrete actions. Given that out‐group prosocial acts in a setting of intergroup conflict may serve as the antecedents for peacebuilding among children and adolescents, this study has intervention implications.